Determining long‐term changes in a skate assemblage with aggregated landings and limited species data. (30th June 2019) - Marandel, Florianne; Lorance, Pascal; Trenkel, Verena M.
Abstract: Sustainable fisheries management requires assessment of exploited populations and communities. Traditional fisheries stock assessment methods need species‐specific input data, which for skates have only recently become available in Europe. To overcome this limitation, a Bayesian multispecies biomass production model was developed. In addition to aggregated landings, input data are short time series with species‐specific information (landings and biomass indices). Applying the approach to four main skate species and a group of two skate species, all managed together in the Bay of Biscay (Northeast Atlantic), long‐term changes in the skate assemblage composition were identified. Since the 1990s, Leucoraja naevus became increasingly dominant, while the contributions of the other three species ( Raja brachyura, Raja clavata and Raja montagui ) declined. The abundance of the grouped Leucoraja fullonica and L. circularis has also strongly decreased, suggesting long‐term overexploitation. All species except this species group are expected to increase over the next decade under current harvest rates. Currently, the species considered here are managed under a single fishing quota making it unlikely that the group of the two most depleted species will recover soon. The multispecies modelling approach bears promise for other harvested assemblages for which only grouped harvest information is available for certain periods.